The Correlation between Mothers’ Knowledge about the Provision of Complementary Foods to Malnutrition Incidence of Children at Binong Public Health Centre - Gusdian Ayu; Silvy Noprisca Br Bangun; Yemima Felicia Ivanna Putri; Fiorentina Nova; Elfrida Silalahi (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2023)
Nutritional problems are still the leading and most common health problems for Children in Indonesia; one of them is malnutrition. In Tangerang, there were 7,863 cases of malnutrition. One of the causes of malnutrition is the provision of complementary foods for children aged 6-24 months which is not appropriate yet. This research aimed to determine the relationship between mothers’ knowledge about the provision of complementary foods for children aged 6-24 months to the incidence of malnutrition at Binong Public Health Centre, Tangerang Regency. This research is a quantitative study with a cross-sectional approach. The population in this study was the mothers with children aged 6-24 months at Binong Public Health Centre, Tangerang Regency, with samples taken using a purposive sampling technique for as many as 90 respondents. The knowledge of the 90 mothers who became the sample was measured through an instrument of knowledge about complementary foods, as well as measuring the nutritional status of children by WHO Child Growth Standards with weight and height data that was taken from January to March 2022. The result of this study showed there is a significant relationship between the mothers’ knowledge about providing complementary foods and malnutrition incidence with a p.value of 0.001 < 0.05. This research is expected to be a source of information about the importance of the mothers’ role in overcoming child nutrition problems in Indonesia which can be done through health education such as counselling about the appropriate provision of complementary foods.